Early detection and monitoring of hearing loss in vestibular migraine: Extended high-frequency hearing - Guo, Zhaoqi; Wang, Jun; Liu, Dan; Tian, E.; Chen, Jingyu; Kong, Weijia; Zhang, Sulin (Frontiers in Aging Neuroscience, 2023)
Background Vestibular migraine (VM) presents mainly with recurrent vestibular symptoms and migraine. A great number of patients with VM have cochlea symptoms such as tinnitus, hearing loss. Methods A cross-sectional study was conducted on patients with definite VM (dVM) and probable VM (pVM) who met the diagnostic criteria. Auditory-vestibular tests and psychological assessments were performed. Logistic regression was used to evaluate the predictive effect of EHF pure tone audiometry (PTA) for standard frequency (SF) hearing loss. Results Fifteen patients with pVM and 22 patients with dVM were recruited. Overall, the two most vertigo types were vestibulo-visual symptoms (83.78%) and internal vertigo (54.05%). A vertigo attack persisted for <5 min in approximately 57% of patients, compared with 5 min to 72 h in 43%, and lasted longer than 72 h in 8%. Approximately 87% of patients had psychological disorders. Most patients with VM (92%) suffered from some degree of EHF hearing impairment, and 68% had SF hearing loss, which is substantially higher than their complaints (43%). Moreover, the mean EHF hearing threshold cutoff value (57 dB HL) worked well in predicting SF hearing loss (area under curve, AUC, 0.827), outperforming distortion product optoacoustic emission (AUC, 0.748). Conclusion VM has a wide range of clinical manifestations. Hearing loss had a considerably higher rate compared to actual complaints. Moreover, patients with VM tended to have bilateral EHF and high-frequency hearing loss. The effectiveness of the mean EHF hearing threshold cutoff value in predicting hearing loss supported its use in the early detection of hearing loss and monitoring disease progression.